2008
DOI: 10.1152/ajpregu.00192.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pyruvate dehydrogenase in the common killifish,Fundulus heteroclitus, during hypoxia exposure.

Abstract: did not parallel one another, suggesting the mitochondrial NADH shuttles do not function during hypoxia exposure. Large increases in the expression of PDK (PDK isoform 2) were consistent with decreased PDH activity; however, these changes in mRNA were not associated with changes in total PDK-2 protein content assessed using mammalian antibodies. No other changes in the expression of other known hypoxia-responsive genes (e.g., lactate dehydrogenase-A or -B) were observed in either muscle or liver. Gibbs free en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 54 publications
5
33
1
Order By: Relevance
“…Killifish are salt marsh residents that spend their entire lifecycle within the marsh, and thus this species has adapted to cope with these stressors (Schulte, 2013). Killifish are among the most extreme eurytherms known among teleost fishes (Fangue et al, 2006), and they are also exceptionally tolerant of hypoxia (Cochran and Burnett, 1996;Richards et al, 2008). Killifish demonstrate a substantial ability to acclimate to a wide range of temperatures (Fangue et al, 2006), and previous studies have demonstrated that thermal acclimation changes ILCM thickness in this species (Barnes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Killifish are salt marsh residents that spend their entire lifecycle within the marsh, and thus this species has adapted to cope with these stressors (Schulte, 2013). Killifish are among the most extreme eurytherms known among teleost fishes (Fangue et al, 2006), and they are also exceptionally tolerant of hypoxia (Cochran and Burnett, 1996;Richards et al, 2008). Killifish demonstrate a substantial ability to acclimate to a wide range of temperatures (Fangue et al, 2006), and previous studies have demonstrated that thermal acclimation changes ILCM thickness in this species (Barnes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Killifish are very tolerant of hypoxia (Richards et al, 2008;Borowiec et al, 2015) and must cope with both seasonal and daily fluctuations in dissolved oxygen in their native estuarine habitat (Tyler et al, 2009). Hypoxia acclimation alters many physiological traits involved in O 2 transport and utilization in this species, including the activity of several oxidative and gluconeogenic enzymes in the liver (Borowiec et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…lactate dehydrogenase), or by reducing carbohydrate flux into the tricarboxylic acid cycle and decreasing aerobic enzyme activity (e.g. cytochrome c oxidase, citrate synthase) (van den Thillart et al, 1980(van den Thillart et al, , 1994Almeida-Val et al, 1995;Martínez et al, 2006;Richards et al, 2008). In addition to mechanisms that help maintain ATP supply, some tolerant organisms can also reduce ATP demands through active depression of resting metabolic rate (van Waversveld et al, 1989;van Ginneken et al, 1997).…”
Section: Introductionmentioning
confidence: 99%